Nitrate levels in well water and population health risk of different planting phases of paddy in Kota Bharu and Bachok, Kelantan Malaysia - Ahmad Roslan, Amirah (2014)
Many researchers found an exposure to nitrate increase the risk getting a cancer. Uncontrolled application of fertilizers on crops cause the excess nitrate to leach into groundwater. This study was conducted to determine the nitrate levels in well water located within 100 meter from paddy farming area in three planting phase. We also determined the health risk associated with the population who used this well water. This study involved 80 wells in Kota Bharu and Bachok Kelantan. Well water samples were analyzed using YSI Professional Plus for nitrate levels while the health risk was calculated using the hazard index formula. Questionnaire was used to obtain the information of the health status of respondents. The mean ± standard deviation (SD) of nitrate levels in Kota Bharu and Bachok was 2.69 ± 2.43 mg/L and 4.02 ± 3.85 mg/L respectively, which was below the national standards (10 mg/L). In general, nitrate concentration higher in planting season with the mean ± SD of 4.63 ± 4.84 mg/L as compared to the pre-planting phase (2.84 ± 2.26 mg/L) and harvesting phase (2.51 ± 2.90 mg/L. The highest nitrate concentration was determined in Bachok during the planting season with the mean ± SD of 6.58 ± 5.89 mg/L. The hazard index for the studied population was less than 1 and ranged between 0.013 and 0.123. There were no respondents reported with gastric cancer cases. In conclusion, the level of nitrate in well water of Kota Bharu and Bachok is tolerable and the population has minimal health risk.